SERTIFIKAT GANDA DAN URGENSI PEMUTAKHIRAN PETA DASAR PENDAFTARAN TANAH - Syukron Salam; Tri Andari Dahlan (Faculty of Law, Universitas Gadjah Mada, 2021)
Abstract This article attempts to uncover the high rate of land disputes in court. The research was conducted by examining court decisions on certificates that overlapped with one another. From court decisions, this research examines the process of overlapped certificates in Semarang City. Regarding the research approach, multiple case study approaches and cross-case analyses were used. The research showed that there were technical problems related to the absence of a comprehensive land registration mapping. The process of modifying regulations on land registrations was not followed by updating the land registration map data. Additionally, the migration process on the former land registration with an analogue mapping system raised problems during migrating or updating the data, specifically on the land registration map data using digital systems. Consequently, the objective of achieving a faster systematic and comprehensive land registration was not achieved and potentially raised legal disputes due to not being preceded by data updates and improvements on the migration mapping process. Intisari Artikel ini mencoba untuk mengetahui fenomena tingginya perkara berobjek tanah yang disengketakan di pengadilan. Penelusuran dilakukan dengan melakukan penelitian terhadap sengketa sertifikat ganda yang telah diputus oleh pengadilan. Berangkat dari putusan pengadilan, penelitian ini menelusuri proses terjadinya sertifikat ganda di Kota Semarang. Penelitian dilakukan dengan menggunakan pendekatan multiple case study dengan menggunakan cross-case analyses. Hasil penelitian menunjukkan adanya permasalahan teknis berkaitan dengan belum terselenggaranya peta pendaftaran tanah yang komprehensif. Proses perubahan peraturan tentang pendaftaran tanah belum dibarengi dengan pemutakhiran data peta pendaftaran tanah. Proses migrasi pendaftaran tanah lama dengan sistem pemetaan analog mengalami kendala ketika dilakukan migrasi atau pemutakhiran data peta pendaftaran tanah dengan sistem digital. Dengan kondisi ini, program percepatan pendaftaran tanah sistematis dan lengkap tanpa didahului dengan pemutakhiran data dan penyempurnaan proses migrasi pemetaan berpotensi menimbulkan masalah hukum.